The effect of the mixing routes of biodegradable polylactic acid and polyhydroxybutyrate nanocomposites and compatibilised nanocomposites. (April 2016) - Gunning, Michael A; Geever, Luke M; Killion, John A; Lyons, John G; Chen, Biqiong; Higginbotham, Clement L
Biodegradable nanocomposites comprising of organically modified montmorillonite-reinforced polylactic acid (PLA) and polyhydroxybutyrate (PHB) were assessed. This study investigates different nanocomposites mixing techniques as methods of achieving exfoliation. The incorporation of reverse flow mixing sections resulted in an increase in exfoliation of nanoclay platelets in PLA nanocomposites. PHB nanocomposites were shown to be more sensitive to thermal degradation and therefore benefited from a reduction in the number of processing steps utilised. Further development of the process was observed with the incorporation of compatibilisers for both polymers which led to considerable improvements in terms of mechanical properties exhibiting superior flexural properties. It was shown using x-ray diffraction that improvements in intercalation was observed which affected the compostability of both composites. Composites with increased interlayer spacing degraded faster and the nanocomposites in general degraded at a faster rate than the virgin polymers.